The Use of Lactic Acid Bacteria and Cellulolytic Bacteria to Improve the Chemical Properties of Corn Flour - Rosyidah, Elly; Meryandini, Anja; Sunarti, Titi Candra (UI Scholars Hub, 2013)
Corn has the potential to be converted into flour, but its hard endosperm causies it to have a coarse particle size, and consequently, corn flour has high crude fiber, low protein, and high moisture. To overcome these problems, the milling of corn grain can be done by steeping it in water. The steeping process causes spontaneous growth of microbes, such as lactid acid bacteria and cellulolytic bacteria. The use of lactid acid bacteria and cellulolytic bacteria in the steeping process can soften the horny endosperm, which can enable corn grits to be ground into fine flours and which can improve the chemical properties of flour passed through an 80-mesh sieve. This study aimed to obtain isolates of indigenous lactid acid bacteria and cellulolytic bacteria from the corn steeping process, and to apply them as a starter in the steeping process of corn grits to improve the fine flour yield, and the chemical properties of flour passed through an 80-mesh sieve. Isolate E2213BAL was the lactid acid bacteria selected as the highest optical density at the logarithmic phase, while isolate B2121SLT was the cellulolytic bacteria with the highest enzyme activity (4.67 mU/ml). The results showed that the use of bacteria starter and fermentation time can decrease pH, increase total acid in the fermentation liquid, decrease the crude fiber, maintain protein, and decrease the moisture of corn flour passed through an 80-mesh sieve.